THE EFFECT OF LIQUIDITY LEVERAGE, INVESTMENT ON THE VALUE OF CONSUMER GOODS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Kiky Ramadhana Yanti; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
The value of the company is an indicator for the market to assess the company as a whole. Company value is a very important element to reflect the company's performance. The higher the value of the company, the welfare of the shareholders also increases. In this study, the factors that influence the value of the company are leverage, liquidity, and investment. In this study, the population used are companies in the consumer goods sector listed on the Indonesia Stock Exchange. The sample obtained as the object of research is as many as 34 companies in the consumer goods sector listed on the Indonesia Stock Exchange. Then the sample was multiplied by 3 years according to the research period, namely 2017 – 2019 so that 102 research observation data were obtained. The analysis technique uses multiple linear regression because it is an equation model that can be used to explain the relationship between two or more independent variables on the dependent variable. Results and Discussion, obtained leverage has no effect on firm value, liquidity has no effect on firm value, investment has a positive and significant effect on firm value.